Partially invertible strongly dependent -ary operations. (February 2020) - Cheremushkin, A. V.
Abstract: We prove analogues of Malyshev's theorems on the structure of finite -quasigroups with the weak invertibility condition and of Belousov's theorem with a description of -associative -quasigroups for the case of strongly dependent -ary semigroup operations on a finite set. Bibliography: 8 titles.